Bridging Gap through Arts and Literature: An analysis of Indo-Pak Print Media Framing - Hassan, Abul; Aamir, Adeel Ahmad; Noor, Rabia (Journal of Peace, Development and Communication, 2022)
Arts and literature play a significant role in bringing the world to a borderless platform with no discrimination of ethnicity, religion and nationality. Sub-continent, especially India and Pakistan are fertile and progressive in literary spheres and share a history of collaborative art production that is progressively hailing in contemporary arts and literature development as well. This study intends to analyze very impression by the print media of India and Pakistan in presenting its arts and literature to their respective and counterpart audiences. 1781 news stories from two Indian and two Pakistani English dailies were purposefully selected to be codified and analyzed for their particular slant and frame. Data revealed that the selected newspapers gave positive coverage to such news stories and unlike eco-political and border conflicts, relied on ‘human interest’ frame as arts and literature are directly related to people than their governments. Study suggest that media’s role in promoting peace and harmony can take advantage of human sentiments of being connected through art and literature and can bridge gap between two rival nations.